Aspek-Aspek Hukum Internasional Dalam Rancangan Undang -Undang Bencana Alam - Jawahir Thontowi (Fakultas Hukum Universitas Islam Indonesia, 2005)
The urgency of the presence of the Natural Disaster Act is due to the fact that a hight tecnology detection used to prevent natural disaster from happening is less effective than the use of legal instrument. In this contexts, however, Indonesian government should in the Draf of Natural Disaster Act acommodate the external components such as, internatinnal convention, status ofIDP's as victims, and foreign assistance and international relief worker. In Addition, The Draf need to explicitly contain certain legal nations like, effort of people's prevention, mitigation, rights and duties, and government responsibility. This includes legal advocacy and the people right to take legal action, when the government faits to fulfil the duties.